Inhibition of the cAMP/PKA/CREB Pathway Contributes to the Analgesic Effects of Electroacupuncture in the Anterior Cingulate Cortex in a Rat Pain Memory Model - Shao, Xiao-Mei (Neural Plast, 2016)
Pain memory is considered as endopathic factor underlying stubborn chronic pain. Our previous study demonstrated that electroacupuncture (EA) can alleviate retrieval of pain memory. This study was designed to observe the different effects between EA and indomethacin (a kind of nonsteroid anti-inflammatory drugs, NSAIDs) in a rat pain memory model. To explore the critical role of protein kinase A (PKA) in pain memory, a PKA inhibitor was microinjected into anterior cingulate cortex (ACC) in model rats. We further investigated the roles of the cyclic adenosine monophosphate (cAMP), PKA, cAMP response element-binding protein (CREB), and cAMP/PKA/CREB pathway in pain memory to explore the potential molecular mechanism. The results showed that EA alleviates the retrieval of pain memory while indomethacin failed. Intra-ACC microinjection of a PKA inhibitor blocked the occurrence of pain memory. EA reduced the activation of cAMP, PKA, and CREB and the coexpression levels of cAMP/PKA and PKA/CREB in the ACC of pain memory model rats, but indomethacin failed. The present findings identified a critical role of PKA in ACC in retrieval of pain memory. We propose that the proper mechanism of EA on pain memory is possibly due to the partial inhibition of cAMP/PKA/CREB signaling pathway by EA.